BOILER INSPECTION PLANNING CFB THERMAL POWER PLANT BASED ON CONDITION PERFORMANCE OF BOILER CASE STUDY PULANG PISAU THERMAL POWER PLANT 2X60 MW - Subekti Muslim Saputra, Ahmad
Boiler is one of the critical equipment of a Steam Power Plant (PLTU) which often causes shutdown units, especially for Circulating Fluidized Bed (CFB) power plant. At present, the method in the planning of boilers inspection is an interesting topic to discuss, as well as the current conditions that occur in the planning of inspections of the CFB type PLTU boiler in the PLN environment specifically at the Pulang Pisau PLTU. The purpose of this study is to discuss boiler inspection planning among them are to predicting the time of boiler inspection implementation, evaluation of boiler pipe inspection intervals and renewal of repair programs that will be carried out during boiler inspection. Boiler Inspection Planning is performed based on the condition performance requirements covers from boiler’s efficiency, pipes thickness and sealpot temperature data.